Effectiveness “Kamio” on Treatment Compliance and Quality of Life Bipolar Disorder Patient in Dr. Iskak General Hospital, Tulungagung, East Java - Prihantoro, Predito; Katmini, Katmini; Puspitasari, Yenny (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Bipolar Disorder is a chronic disease with various variations in the course of the disease that are often unknown, misdiagnosed and even when diagnosed are often not adequately treated. The aim of the study was to analyze the effectiveness of KamiO on quality of life in Bipolar Disorder patients at dr. Iskak Tulungagung Hospital.Subjects and Method: Observational study with randomized control trial was conducted at dr. Iskak General Hospital, Tulungagung, East Java, from May 25 to August 25, 2022. The study population were 160 patients with bipolar disorder. A 114 sample was selected using the simple random sampling divided into (1) 57 sample in the treatment group and (2) 57 sample in control group. In this study, the independent variable was KAMIO. The dependent variable is medication adherence and quality of life. While the measuring instrument used is a questionnaire. Data analysis using Mann Whitney test.Results: Patients in the intervention group more adherent to visit medical treatment (Mean= 63.00) than control group (Mean= 52.00), with p= 0.039. Quality of life in bipolar disorder patients in the intervention group (Mean= 72.25) was higher than in the control group (Mean= 42.75) and it was statistically significant (p<0.001).Conclusion: Quality of life in the intervention group (kamio cards) is higher than in the control group.Keywords: kamio effectiveness, treatment adherence, quality of life, bipolarCorrespondence: Katmini. STRADA Indonesian Institute of Health Sciences. Jl. Manila No. 37, Kediri, East Java 64123, Indonesia. Email: katminitini@gmail.com. Mobile: 0823-3466-2921.Indonesian Journal of Medicine (2022), 07(03): 337-343https://doi.org/10.26911/theijmed.2022.07.03.10